1999
DOI: 10.1039/a903817e
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Self Coupling of 4-Oxo-4H-1-benzopyran-3-carboxaldehyde

Abstract: The title aldehyde 1 gives the bischromones 2, 3 and disalicyloylbenzene 5 with sodium naphthalenide; a mixture of 3 and chromanone 22 with zinc in methanol; 3, carbinol 6 and diol 8 with zinc in acetic acid; and acetates 7 and 9 with Zn^Ac 2 O^AcONa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…It may be mentioned here that the melting point of the major product (meso isomer) i.e., meso-1,2-dihydroxyethylenebis(chromen-4-one) (Fig. 1) obtained by us was the same as that of the stereoisomer of 1 reported by Bandyopadhyay et al 14 So, it is interesting that there was no indication for the formation of minor 1,2-diol product in the report of Bandyopadhyay et al 14 although it was formed during our reaction.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…It may be mentioned here that the melting point of the major product (meso isomer) i.e., meso-1,2-dihydroxyethylenebis(chromen-4-one) (Fig. 1) obtained by us was the same as that of the stereoisomer of 1 reported by Bandyopadhyay et al 14 So, it is interesting that there was no indication for the formation of minor 1,2-diol product in the report of Bandyopadhyay et al 14 although it was formed during our reaction.…”
supporting
confidence: 85%
“…[9][10][11][12][13] In connection with our study of the reaction of different oxygen heterocycles having unsaturated carbonyl moiety, in modified Clemmensen reduction condition, we have considered 4-oxo-4H-chromene-3-carbaldehyde as easily available starting material. Concurrent to this work, Bandyopadhyay et al 14 reported the formation of only one 1,2-diol compound from 4-oxo-4H-chromene-3-carbaldehyde in modified Clemmensen reduction condition and they did not mention the configuration of their reported compound. Formation of only one 1,2-diol compound from 4-oxo-4Hchromene-3-carbaldehyde encouraged us to reinvestigate the reaction under similar reaction conditions.…”
mentioning
confidence: 84%
“…Bandyopadhyay et al 13 have reported the coupling of chromone-3-carbaldehydes in the presence of various reagents to give bis-chromones, while Wähälä and co-workers 14 have described the synthesis of three unique C-C-bridged bis-isoflavones. To our knowledge, however, the formation of the dimeric products 4a-e is unprecedented.…”
mentioning
confidence: 99%